SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMILIH LAPTOP IDEAL DENGAN METODE SAW - jamrud khatulistiwa; Wahyu Nur Fadillah; Mohammed Hafizh Al-Areef (E-Jurnal Universitas Samudra, 2023)
Laptops are one of the tools that are widely used in today's modern era, with a portable design that is able to meet the needs of everyday work. To facilitate the selection of a laptop that is comfortable and in suitable with the needs of the work, a decision support system is needed to assist users in choosing the right laptop. This system uses the Simple Additive Weighting method which is a weighted addition method from all existing data. The results of the research are in the form of a decision support system application in choosing the ideal laptop based on a website that can make it easier for users to choose the ideal laptop and according to their needs based on predetermined laptop criteria